Are Thyroid Functions Effective in Pregnant Women with Hyperemesis Gravidarum? - Güler, Aşkın Evren; Yıldız, Birol; Çakmak, Bülent; Demirel Güler, Zeliha Çiğdem; Kıncı, Mehmet Ferdi (Cerrahpaşa Medical Journal, 2019)
Objective: This study aims to detect the role of thyroid hormones in the etiology of hyperemesis gravidarum (HG), which has apparent adverse effects on fetal and maternal outcomes. Methods: In this study, we retrospectively evaluated 1634 term primiparous cases of single-birth deliveries (37–42 weeks of gestation) at the Koru Hospital Ankara between November 2012 and September 2014. Maternal age, existence of any treatment during pregnancy, the history of alcohol consumption before pregnancy, smoking habits, and newborn’s gender were detected. The first-trimester HG cases and thyroid-stimulating hormone (TSH) and free tyroxine (fT4) levels were recorded. Results: Compared with other two groups, the TSH level was lower in the HG group, while the fT4 level was higher. Despite this fact, no statistical significance was detected (p=0.06). Compared with other groups, maternal age was significantly lower in the group with HG and was thus statistically significant (p=0.01). Conclusion: In HG pregnancies, the thyroid-metabolism-related disorders and maternal age should be kept in mind, and laboratory-clinical analyses and early diagnosing and treatment should be considered. Cite this article as: Güler AE, Yıldız B, Çakmak B, Demirel Güler ZÇ, Kıncı MF. Are Thyroid Functions Effective in Pregnant Women with Hyperemesis Gravidarum?. Cerrahpasa Med J 2019; 43(3): 80-84.